Gender–responsive public space: An inclusivity perspective toward sustainable urban development - Rika Triyunia Savitri (Journal of Placemaking and Streetscape Design, 2026)
Background:  Gender-inclusive public spaces play a crucial role in supporting social interaction, safety, and economic participation for diverse user groups, particularly women and vulnerable communities. In the Indonesian urban context, the integration of gender–responsive architectural principles in public space design remains uneven and is often constrained by normative and policy-oriented approaches. This study aims to identify key principles of gender–responsive architecture and examine their relevance to social and economic impacts in public spaces. Methods: This research adopts a qualitative descriptive approach using document analysis. Data were collected from international guidelines, national policies, and academic literature related to gender–responsive planning, inclusive design, and public space development. The documents were selected based on relevance and credibility, and analyzed using thematic coding to identify recurring architectural principles and their associated social and economic implications. Findings: The findings reveal several core principles of gender–responsive architecture in public spaces, including accessibility, safety, visibility, spatial legibility, and universal design. These principles are closely associated with positive social outcomes such as increased sense of safety, social interaction, and inclusiveness, as well as economic impacts through the activation of informal economic activities, micro-enterprises, and community-based creative initiatives. Conclusion: The study concludes that gender–responsive architectural principles provide an essential framework for creating inclusive and human-centered public spaces in Indonesia. By systematically linking design principles with social and economic outcomes, this research contributes to a more comprehensive understanding of gender-inclusive public space development. Novelty/Originality of this article: This article offers an original contribution by systematically synthesizing gender–responsive architectural principles and explicitly linking them to social and economic impacts in Indonesian public spaces, thereby advancing human-centered public space design and placemaking evaluation within urban streetscape and public realm studies.